Mechanical and durability properties of recycled aggregate concrete produced from recycled and natural aggregate blended based on the Densified Mixture Design Algorithm method - Vo, Duy-Hai; Yehualaw, Mitiku Damtie; Hwang, Chao-Lung; Liao, Min-Chih; Tran Thi, Khanh-Dung; Chao, Yu-Fan (Journal of Building Engineering, 2021)
The aim of this study was to reuse recycled concrete aggregates for concrete production by using the Densified Mixture Design Algorithm (DMDA) method for blended aggregates and mixing design based on the evaluation of characteristics of recycled aggregate concrete (RAC). Recycled coarse aggregate (RCA) was used to replace 30%, 40%, and 50% of the natural coarse aggregate (NCA), respectively, by volume in the samples, and the fine aggregate was a combination of 70% natural fine aggregate (NFA) and 30% recycled fine aggregate (RFA) by volume. A series of tests, including compressive strength, splitting tensile strength, ultrasonic pulse velocity (UPV), electrical surface resistivity (ESR), thermal conductivity (TC), water absorption, and the rapid chloride penetration test (RCPT) were conducted in accordance with the relevant standards. The results illustrated that blending aggregates following to DMDA method suggested an optimum proportion of RCA level which exhibited with highest volume of aggregate per unit volume of combination of RCA and NCA. The results revealed 40% RCA content as the optimum replacement level. Furthermore, the 40% RCA concrete mix exhibited good hardening properties in terms of being only slightly below the 30% RCA mix and significantly higher than the 50% RCA mix. All of the RAC mixtures designed by DMDA method with low cement consumption exhibited good strength development and good durability through 120 days of curing. •The RAC was produced using blended recycled and natural aggregates and low cement content based on the DMDA method.•The blended aggregate was created to obtain a high amount of RA content and minimal negative effects on concrete properties.•The RAC specimens designed using the DMDA method exhibited good strength and durability.